Simulation of low-latitude ionospheric response to 2015 St. Patrick’s Day super geomagnetic storm using ionosonde-derived PRE vertical drifts over Indian region - Joshi, L.M.; Sripathi, S.; Singh, Ram (My University, 2016)
In this paper, we present low-latitude ionospheric response over Indian longitude to the recent super geomagnetic storm of 17 March 2015, using the Sami2 is Another Model of the Ionosphere (SAMI2) model which incorporates ionosonde-derived vertical drift impacted by prompt penetration eastward electric field occurring during the evening prereversal enhancement (PRE) in the vertical drift. The importance of this storm is that (1) Dst reaches as low as 228 nT and (2) prompt penetration of eastward electric field coincided with evening hours PRE. The daytime vertical E × B drifts in the SAMI2 model are, however, considered based on Scherliess-Fejer model. The simulations indicate a significant enhancement in F layer height and equatorial ionization anomaly (EIA) in the post sunset hours on 17 March 2015 vis-a-vis quiet day. The model simulations during recovery phase, considering disturbance dynamo vertical E × B drift along with equatorward disturbance wind, indicate suppression of the daytime EIA. SAMI2 simulations considering the disturbance wind during the recovery phase suggest that equatorward wind enhances the ionospheric density in the low latitude; however, its role in the formation of the EIA depends on the polarity of the zonal electric field. Comparison of model derived total electron content (TEC) with the TEC from ground GPS receivers indicates that model does reproduce enhancement of the EIA during the main phase and suppression of the EIA during the recovery phase of the superstorm. However, peculiarities pertaining to the ionospheric response to prompt penetration electric field in the Indian sector vis-a-vis earlier reports from American sector have been discussed.
Keywords: TEC; Total electron content; Super geomagnetic storm; Geomagnetic storms; Patrick’s Day 2015; SAMI2; Scherliess-Fejer model